2004
DOI: 10.1016/s0749-8063(04)00812-6
|View full text |Cite
|
Sign up to set email alerts
|

Revision anterior cruciate ligament reconstruction with nonirradiated fresh-frozen patellar tendon allograft

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
60
3

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 0 publications
8
60
3
Order By: Relevance
“…Our results after ACL revision using allogenous materials are comparable with those of Fox et al [15] and Johnson et al [22].…”
Section: Discussionsupporting
confidence: 91%
“…Our results after ACL revision using allogenous materials are comparable with those of Fox et al [15] and Johnson et al [22].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies reported a global IKDC A ? B rate between 12 and 83% [14,15,17,22,27,30,41]. Considering the same criteria for failure previously used in the literature, the 11% failure rate reported in this study is consistent with that reported recently by Ferretti et al [13], Salmon et al [32], Denti et al [11], and Muneta et al [26].…”
Section: Discussionsupporting
confidence: 89%
“…Most studies on ACL revision are focused on a specific surgical technique and different grafts [6,20,21]. Some examine results of ACL revision seen at a specialized center [22,23].…”
Section: Discussionmentioning
confidence: 99%